Indeks vlažnosti tal Pomurja - Davidović, Danijel (Revija za geografijo, 2020)
This research demonstrates the methodological implementation of satellite imagery for evaluation of soil moisture in the case of Pomurje (Slovenia). The presented soil moisture index is a derivative of surface temperature and NDVI vegetation index, using spectral bands detected by optical and thermal sensor of the Landsat 8 satellite. The obtained values of the soil moisture index vary between 0 (low soil moisture) and 1 (high soil moisture). Furthermore, we observe the differences in soil moisture with regard to intensive or extensive agricultural land use. The calculated estimates of soil moisture in Pomurje reached values between 0.06-0.99, with statistically significant differences between higher values in forests and lower values in fields and other selected landuse categories. This approach to soil moisture assessment is useful for monitoring and planning agricultural and environmental activities at the landscape level and for evaluating the climate change impact on the humidity conditions in a given area.
Keywords: daljinsko zaznavanje; geografski informacijski sistemi; geographic information system; indeks vlažnosti tal; land surface temperature; Landsat; normalized difference vegetation index; normiran diferencialni vegetacijski indeks; remote sensing; soil moisture index; temperatura površja